(untitled) (Cadernos de Sociomuseologia, 2015)
By bringing together existing literature on the wider repatriation debate, and examining how different strands within the discussion influence, benefit or constrain one another, it is the hope of the author that this work will add to, weave together and potentially illuminate existing scholarly and professional discussion of repatriation from museum collections, with a view to understanding how these interactions will continue to build or develop in future. This is neither a justification nor an exploration of a particular stance on this contentious issue in museum practice, but rather an investigation of the inner workings of the repatriation movement and the legislation, professional obligations and discussion which surround it. Keywords: Repatriation; cultural proprerty; museology